2020
DOI: 10.5194/esurf-2020-93
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverse modeling of turbidity currents using artificial neural network: verification for field application

Abstract: Abstract. Although in situ measurements observed on modern frequently occurring turbidity currents have been performed, the flow characteristics of turbidity currents that occur only once every hundreds of years and deposit turbidites over a large area have not yet been elucidated. In this study, we propose a method for estimating the paleo-hydraulic conditions of turbidity currents from ancient turbidites by using machine learning. In this method, we hypothesize that turbidity currents result from suspended s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In the case of turbidity currents, however, it is impossible to obtain sufficient data sets of in‐situ measurements of flow characteristics for developing a DNN inverse model. Instead of using in‐situ measurements of turbidity currents in nature, Naruse and Nakao (2020) generated numerical data sets of turbidites using a forward model. The generated data sets were input into a DNN model to explore the functional relationship between turbidites and initial flow conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of turbidity currents, however, it is impossible to obtain sufficient data sets of in‐situ measurements of flow characteristics for developing a DNN inverse model. Instead of using in‐situ measurements of turbidity currents in nature, Naruse and Nakao (2020) generated numerical data sets of turbidites using a forward model. The generated data sets were input into a DNN model to explore the functional relationship between turbidites and initial flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…After this network training process, the DNN model can estimate flow conditions from new turbidite data. Naruse and Nakao (2020) performed inverse analysis using a trained DNN model on field scale numerical test data sets generated by a forward model. Their results showed that the DNN model can reconstruct flow properties from numerical test data sets and was robust against noise in input data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous methods to estimate flow conditions for turbidites were either overly simplified (Baas et al, 2000), incapable of reproducing graded beds (Falcini et al, 2009), accurate but computationally intractable for natural scale turbidity currents (Lesshafft et al, 2011), or low in accuracy (Parkinson et al, 2017), a method that is both accurate and not computationally intractable should be developed. To resolve the aforementioned issues, Naruse and Nakao (2020) proposed a new method for inverse analysis of turbidite deposits using deep learning neural networks (DNN). A DNN model is a machine-learning computing system that works as a universal function approximator (Liang & Srikant, 2016), meaning that an unknown function governing the relationship between observations within a domain is explored and approximated.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of turbidity currents, however, it is impossible to obtain sufficient data sets of in-situ measurements of flow characteristics for developing a DNN inverse model. Instead of using in-situ measurements of turbidity currents in nature, Naruse and Nakao (2020) generated numerical data sets of turbidites using a forward model. The generated data sets were input into a DNN model to explore the functional relationship between turbidites and initial flow conditions.…”
Section: Introductionmentioning
confidence: 99%